1974
DOI: 10.1901/jeab.1974.22-61
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF THE DIFFERENCE BETWEEN SELF AND COACTOR SCORES UPON THE AUDIT RESPONSES THAT ALLOW ACCESS TO THESE SCORES1

Abstract: An audit response allows access to an existing score from a subject's own performance (self audit) or from his coactor's performance (coactor audit), A previous study found that social stimuli (coactor present) increased audits relative to a non-social (no coactor) condition. The increase, designated a social-stimulus effect, was found to be due more to the coactor's score than to his mere presence. This finding suggested that the difference between self and coactor scores might affect the size of the social-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0
1

Year Published

1980
1980
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
2
7
0
1
Order By: Relevance
“…These differences likely account for the more frequent auditing in 100%/0% contests, particularly those in which partners were evenly matched. This result is consistent with earlier findings of more frequent auditing with small score discrepancies (Buskist & Morgan, 1988;Vukelich & Hake, 1974). Consistent with the greater reinforcing effects of good news, auditing was more frequent by winners than losers regardless of distribution, but winners did not consistently choose to view such news (i.e., audit rates were well below the maximum).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These differences likely account for the more frequent auditing in 100%/0% contests, particularly those in which partners were evenly matched. This result is consistent with earlier findings of more frequent auditing with small score discrepancies (Buskist & Morgan, 1988;Vukelich & Hake, 1974). Consistent with the greater reinforcing effects of good news, auditing was more frequent by winners than losers regardless of distribution, but winners did not consistently choose to view such news (i.e., audit rates were well below the maximum).…”
Section: Discussionsupporting
confidence: 91%
“…Each audit response consisted of five responses on a lever, and provided information concerning the other's score (coactor audits). In both studies, auditing was more frequent when scores were similar than when large discrepancies developed, consistent with Vukelich and Hake's (1974) findings. In the second study, they also found auditing by subjects who were behind during competition, but not by ones who were far ahead.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…These two response domains may be functionally related: An initially high rate of interpersonal auditing under conditions of positive reinforcement may indicate, as a behavioral "marker" of individual differences, sensitivity to disruptive reactions when inequity exists under conditions of negative reinforcement. The importance of measuring several concurrent responses has also been demonstrated with human behavior analyses where a person's rate of auditing his and anothers performance "score," produced within the context of a dyadic social relationship, was interpretable in terms of other observations (Hake, Vukelich, & Kaplan, 1973;Vukelich & Hake, 1974). High rates of auditing in both situations may be functionally related to a subject's low level of "trust" that an equitable relationship between work and reinforcers will prevail over time (Hake & Schmid, 1981;Schmid & Hake, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…(Dougherty & Cherek, 1994;Hake, Vukelich, & Kaplan, 1973;Schmitt, 1998Schmitt, , 2000Vukelich & Hake, 1974). Porém, tais estudos têm investigado o efeito desta variável em respostas competitivas e não em respostas "cooperativas", no Jogo Dilema do Prisioneiro Repetido.…”
Section: Os Participantes Dos Três Experimentos Foram Submetidos Ao Junclassified